2002
DOI: 10.4269/ajtmh.2002.67.490
|View full text |Cite
|
Sign up to set email alerts
|

Short report: seasonal pattern of respiratory syncytial virus in a region with a tropical climate in southeastern Brazil.

Abstract: Abstract. Among acute respiratory infections (ARIs), respiratory syncytial virus (RSV) is an important pathogen, especially in infants and preschool children. This study focused on RSV epidemiology in a region of southeastern Brazil with a tropical climate. A total of 406 nasopharyngeal secretion samples were taken from children less than five years of age with ARIs. Of these, 114 (28%) were RSV-positive. These samples were found in all age groups, but showed a higher prevalence in newborns. Infection with RSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
22
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 18 publications
7
22
0
2
Order By: Relevance
“…In this study, RSV was detected from February to June (late summer to late autumn), with peak in April and May (autumn), as similarly related in Ribeirão Preto (SP) by Cintra et al (2001) and in Vitória (ES) by Checon et al (2002), and has not been detected in other months. In regions with lower temperatures during winter, such as São Paulo (Vieira et al 2001), Botucatu (Bosso et al 2004), and Porto Alegre (Strallioto et al 2001) cities, RSV circulation extended to July or August (mid-winter).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In this study, RSV was detected from February to June (late summer to late autumn), with peak in April and May (autumn), as similarly related in Ribeirão Preto (SP) by Cintra et al (2001) and in Vitória (ES) by Checon et al (2002), and has not been detected in other months. In regions with lower temperatures during winter, such as São Paulo (Vieira et al 2001), Botucatu (Bosso et al 2004), and Porto Alegre (Strallioto et al 2001) cities, RSV circulation extended to July or August (mid-winter).…”
Section: Discussionmentioning
confidence: 54%
“…of age. Some reports have shown that the RSV is a frequent cause of acute respiratory infections in children younger than five years old, with incidence reaching 17% , 18% (Bosso et al 2003), 22% (Cintra et al 2001), and 28% (Checon et al 2002) of the investigated cases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Brazilian data about the pattern of RSV infection and circulation of the RSV groups have been obtained mostly from cities in the Southeastern, Southern and Northern regions , Mello & Silva 1992, Sutmoller et al 1995, Cintra et al 2001, Vieira et al 2001, Straliotto et al 2001, Checon et al 2002.…”
mentioning
confidence: 99%
“…These epidemics have been reported to vary according to the local, and are influenced by climatic factors variation (Checon et al 2002). Associations between respiratory viruses presence with temperature, rainfall and relative air humidity have been adopted in epidemiological studies worldwide (Viegas & Mistchenko, 2005).…”
Section: Discussionmentioning
confidence: 99%